Days of Alcohol and Roses - Iruela, Luis M. (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
Alcoholism is a condition with far- reaching effects on social and emotional life. This article deals with the core sense of alcoholism, shame, based on an analysis of the movie Days of wine and roses.